The effects of ankle joint taping on gait and balance ability of healthy adults - Kim, Myoung-Kwon (J Phys Ther Sci, 2015)
[Purpose] This study examined the effects of the application of elastic taping over the ankle joints of healthy subjects on their gait, balance ability, and muscle strength. [Subjects] Fifty healthy subjects with no orthopedic history of the ankle joint were selected and elastic taping was applied to their ankle joints. [Methods] Before and after application of the elastic taping, gait and balance ability of the subjects were evaluated. [Results] After the taping application, gait velocity significantly increased and there were significant differences in all variables of balance ability. [Conclusion] Application of elastic taping aimed at improving stability of the ankle joint had a positive effect on gait speed and balance ability.